Case Report: Successful Treatment of Steroid-Refractory Immune Checkpoint Inhibitor-Related Pure Red Cell Aplasia With Cyclosporin - Alexandre Gérard; Serena Romani; Elise Van-Obberghen; Audrey Fresse; Marine Muzzone; Nadège Parassol; Annick Boscagli; Fanny Rocher; Delphine Borchiellini; Milou-Daniel Drici (Frontiers in Oncology, 2020)
Anemia associated with Immune checkpoint inhibitor (ICI) is usually hemolytic and regenerative. Cases of non-regenerative pure red cell aplasia are rare, and typically improve upon drug discontinuation and after corticotherapy. We herein report a case of nivolumab-related erythroblastopenia refractory to steroids in a melanoma patient that improved only after treatment with cyclosporin. Nivolumab had been well tolerated for 2 months after being introduced as an adjuvant treatment. Hemoglobin level then progressively decreased from 12.7 g/dl as baseline value to a nadir of 4.3 g/dL despite transfusion with a total of 29 packed red blood cells in 3 months. Extensive workup including repeated bone marrow examinations led to the diagnosis of pure red cell aplasia. Anemia persisted despite nivolumab discontinuation and over a month of corticotherapy, but improved dramatically 3 days after cyclosporin initiation and did not recur upon cyclosporin tapering. The patient remains cancer-free 9 months after nivolumab withdrawal. This case highlights the under-recognized risk of erythroblastopenia in patients treated with ICI and proves cyclosporin is a valid alternative for the treatment of steroid-refractory cases.